High expression of miR-7974 predicts poor prognosis and is associated with autophagy in estrogen receptor-positive breast cancer - Stralina Eneh; Jaana M. Hartikainen; Sami Heikkinen; Reijo Sironen; Maria Tengström; Veli-Matti Kosma; Saket Ahuja; Arto Mannermaa (PLoS ONE, 2025)
Estrogen receptor-positive (ER+) breast cancers (BC) cause death despite well-established treatments. MicroRNAs (miRNAs) have potential as biomarkers specific to cancer subtypes and tissues, therefore miRNA-based biomarkers could help improve patient survival. In this study, we investigated a relatively unknown miRNA, miR-7974. We utilized small RNA data from 204 breast tissue samples to study miR-7974 association with clinicopathological features and outcomes for BC patients. Additionally, in vitro and in ovo methods were used to identify miR-7974 role at molecular and cellular level in MCF-7 cells. Findings were validated using MDA-MB-453 cells. MiR-7974 was upregulated in many clinicopathological features of BC (P<0.05). Furthermore, the highest expression of miR-7974 was associated with poor relapse-free survival in ER+ BC patients [hazard ratio (HR)=8.70; 95% confidence interval (CI)=3.28–23.06; P=1.37x10-05] and poor BC-specific survival in patients receiving only surgical treatment (HR=8.36; 95% CI=1.01–69.06; P=0.049). Our studies revealed that miR-7974 targets autophagy gene, MAP1LC3B, identified as direct miR-7974 target (P<0.05) in MCF-7 cells. In vitro analyses indicated overexpressing miR-7974 had anti-proliferative effect in MCF7 and MDA-MB-453 cells. Overall, our results demonstrate potential prognostic role of miR-7974 in ER+ BC.